Reviewing Mental Revolution from Islamic Education Perspective - Wahyu Dwi Yulianto; Kurniawan Dwi Saputra (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2021)
In order to accelerate economic and political power, starting from President Jokowi speech before DPD (Regional Representative Council), the government organize Gerakan Nasional Revolusi Mental (GNRM). This paper seeks to scrutiny the meaning of mental revolution, a priority program of the Indonesian government to produce citizen with character to be ready to compete in the global era, from the perspective of Islamic education. This study uses qualitative methods through a literature review, then the data is explained through descriptive analysis technique. This research will examine mental revolution from the perspective of Islamic education; background and goals of mental revolution. The conclusion of this study is that Islamic education is in line with mental revolution program as proposed by Indonesian government in cultivating good character towards human. However, while mental revolution program is instrumental due to its pragmatic objectives, Islamic education is more essential as it views akhlak as the most important objective of education